Pengaruh model discovery learning terhadap hasil belajar siswa pada materi tabung di SMP negeri 1 panyabungan - Ilyas Reski Aziz; Bintang Zaura; Khairul Umam (IKIP Siliwangi, 2025)
This research aims to see the influence of the discovery learning model on students' mathematics learning outcomes in tube material in class IX. Quasi experimental design. The post-test control group used by researchers uses a quantitative approach. All students in class IX of SMPN 1 Panyabungan are the population of the research, while the sample consists of two classes, namely classes IX-1 and IX-2, each class consists of 22 students selected using purposive sampling techniques. The research instrument used was a learning outcomes test in the form of a final test (post-test), which consisted of 8 essay questions. Data analysis techniques include a normality test to ensure that the data is normally distributed, a homogeneity test to check the equality of variance between groups, and hypothesis testing using the t-test to determine the significance of differences in learning outcomes between the experimental and control groups. The results of the data analysis process obtained show that the calculated t-value is 9.706, which is higher than t-table value of 2.018 at the 5% significance level. This shows that the discovery learning model influences student learning outcomes in class IX curved-sided geometric shapes (tube) material at SMP Negeri 1 Panyabungan.